ISTRI SEBAGAI PELAKU TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA : SUATU KAJIAN KRIMINOLOGIS - Ni Gusti Agung Ayu Mas Tri Wulandari (Media Bina Ilmiah, 2023)
Cases of Domestic Violence (hereinafter written KDRT) are a form of crime that occurs in society. Violent crime is essentially a manifestation of human behavior. This violence is understood as gender-based violence or gender violence. This concept actually refers to the subordinated position of women because the relationship between the two reflects powerless and powerful, in other words, there is an imbalance of power between women and men. Wives tend to be victims of domestic violence, and repetition of violence tends to be experienced by a wife. Under certain conditions, a wife can fight back and commit domestic violence against other family members within the household. An outside non-legal approach is needed to handle it. In addition to the victimological approach, as a way to solve and or overcome the crime of domestic violence, an approach from the aspect of criminology is also needed. Because criminology can be a bridge for crime prevention efforts as well as providing preventive ammunition. Classical Criminology with its penalizing ammunition, Positivistic Criminology with criminal etiology (looking for the causes of crime) and critical criminology with criminal sociology will very likely contribute to efforts to minimize cases of domestic violence